2013
DOI: 10.1186/1748-5908-8-17
|View full text |Cite
|
Sign up to set email alerts
|

How hard can it be to include research evidence and evaluation in local health policy implementation? Results from a mixed methods study

Abstract: BackgroundAlthough an evidence-based approach is the ideal model for planning and delivering healthcare, barriers exist to using research evidence to implement and evaluate service change. This paper aims to inform policy implementation and evaluation by understanding the role of research evidence at the local level through implementation of a national chronic conditions management policy.MethodsWe conducted a national email survey of health service commissioners at the most devolved level of decision-making i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 36 publications
6
73
2
Order By: Relevance
“…Monash Health is not unique and these issues are commonplace in health services around the world [8, 40, 44, 51, 5760]. This indicates enormous opportunities for improvement through strategies that address these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Monash Health is not unique and these issues are commonplace in health services around the world [8, 40, 44, 51, 5760]. This indicates enormous opportunities for improvement through strategies that address these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Framework drew on literature available at its time of development (2012), subsequent work (e.g. Brown, 2012;Ettelt et al, 2013;Evans et al, 2013;Moat et al, 2013;Oliver et al, 2014;Panisset et al, 2012;Pitchforth et al, 2013;Yost et al, 2014) have largely confirmed previous reviews and the basis of the Framework.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is a lack of information to guide local healthcare services regarding an organisational approach to disinvestment [312]. …”
Section: Introductionmentioning
confidence: 99%